2016
DOI: 10.7206/jmba.ce.2450-7814.164
|View full text |Cite
|
Sign up to set email alerts
|

The Adaptation of the Motivation to Lead Instrument to the Estonian Military Context

Abstract: Purpose: This study is a contribution to the validation of the Motivation to Lead (MTL) scale proposed by Chan and Drasgow (2001) in order to measure three types of motivation to be a leader: affective, social-normative and calculative. This research examines the psychometrical properties of the MTL scale in the Estonian context. Methodology:The sample of 517 military and non-military individuals from the Estonian Defence Forces, Estonian Police and students from Tallinn University participated in the study. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Specifically, it was examined whether he three-factor structure of the proposed MTL scale was consistent with that in previous studies (i.e., AI-MTL, NC-MTL, and SN-MTL; Chan and Drasgow, 2001). Since previous studies present inconsistent results concerning the original version's factor structure (Bobbio and Rattazzi, 2006;Amit et al, 2007;Kasemaa, 2016), this study also investigated alternative models. The following goodness-of-fit indices were adopted: comparative fit index (CFI), root mean square error of approximation (RMSEA), and standardized root mean square residual (SRMR).…”
Section: Analysis Proceduresmentioning
confidence: 88%
See 4 more Smart Citations
“…Specifically, it was examined whether he three-factor structure of the proposed MTL scale was consistent with that in previous studies (i.e., AI-MTL, NC-MTL, and SN-MTL; Chan and Drasgow, 2001). Since previous studies present inconsistent results concerning the original version's factor structure (Bobbio and Rattazzi, 2006;Amit et al, 2007;Kasemaa, 2016), this study also investigated alternative models. The following goodness-of-fit indices were adopted: comparative fit index (CFI), root mean square error of approximation (RMSEA), and standardized root mean square residual (SRMR).…”
Section: Analysis Proceduresmentioning
confidence: 88%
“…Previous studies have indicated that collectivism is a cultural characteristic of Japan (Bergiel et al, 2012). Given that NC-MTL is positively correlated with collectivist values rather than with individualistic values (Chan and Drasgow, 2001;Kasemaa, 2016;Badura et al, 2020), Japan's highly collectivist culture may influence NC-MTL compared with countries with more individualistic cultures.…”
Section: Construct Validitymentioning
confidence: 99%
See 3 more Smart Citations